Methods and prospects for lithospheric structure imaging - Bin Shan; Wanli Zhou (地质科技通报, 2022)
In recent years, with rich observation data, the perfection of physical chemistry theory and the remarkable improvement of computer technology, great changes have taken place in the understanding of lithospheric physical and chemical properties. This paper introduces the current imaging methods of lithospheric structure and their advantages and disadvantages. Based on thermodynamic simulation and probability density inversion, we study the lithospheric thermal and compositional structure in South China (Sichuan Basin, Jiangnan Orogenic Belt, Lower Yangtze Craton and Cathaysian Block)using the observed Rayleigh wave phase velocity dispersion curve, geoid height, topography and surface heat flow. The results show that the lithosphere in the east of South China block is thin, and the lithospheric mantle is dominated by fertile peridotite, while the subduction of the Pacific plate from east to west may be the main dynamic mechanism of lithospheric thinning in the east of South China.Finally, we introduce the existing problems of lithospheric structure imaging and the prospect of future lithospheric structure imaging based on the current research status of lithospheric structure.